Influence of urbanity on perception of mental illness stigma: a population based study in urban and rural Hanoi, Vietnam. (December 2016) - Ta, Thi Minh Tam; Zieger, Aron; Schomerus, Georg; Cao, Tien Duc; Dettling, Michael; Do, Xuan Tinh; Mungee, Aditya; Diefenbacher, Albert; Angermeyer, Matthias C; Hahn, Eric
Background and Aims: To examine, for the first time in Vietnam, whether urbanity of respondents among other socio-demographic factors affects the public perception of stigma attached to persons with mental illness in Hanoi. Methods: A general population-based survey was carried out in 2013 in the greater Hanoi area. The perception of stigma attached to people with mental illness was elicited using Link's perceived discrimination and devaluation scale (PDDS) carried out in Vietnamese language. The survey sample ( n = 806) was stratified for gender, urban/rural location, age, household size and marital status, in accordance with the 2013 Vietnamese census. Results: Comparing the total score of the PDDS and its single items, we found less perceived stigma and discrimination among the rural population of Hanoi and in respondents who reported religious attainment to either Buddhism or Christianity. Logistic regression analyses found no significant influences of gender, age, household size or marital status regarding the perceived stigma toward persons with mental illness. Conclusion: Less negative perception of stigma attached to persons with mental illness that was observed among the rural population in the Hanoi area may be interpreted in the light of possibly more demanding living conditions in modern urban Vietnam with less opportunities for mentally ill patients and points toward a dynamic interaction with rapidly changing living conditions in Asian megacities.